2016
DOI: 10.20471/acc.2016.55.s1.12
|View full text |Cite
|
Sign up to set email alerts
|

Upper Airway Blocks for Awake Difficult Airway Management

Abstract: SUMMARY -Airway anesthesia is pivotal for successful awake intubation provided either topically or by blocks. Airway blocks are considered technically more difficult to perform and carry a higher risk of complications. However, in experienced hands, they can be useful as they provide excellent intubating conditions. For complete upper airway anesthesia, bilateral glossopharyngeal and superior laryngeal nerve blocks with translaryngeal injection are required. Superior laryngeal nerve block and translaryngeal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Airway blocks can be performed easily and safely in patients with normal anatomy. In those with difficult landmarks, ultrasound can be of assistance [23]. We did not use ultrasound at the time of the study but have since implemented this for difficult cases.…”
Section: Kramer Et Al Described the Necessity Of Stylets In 23mentioning
confidence: 99%
“…Airway blocks can be performed easily and safely in patients with normal anatomy. In those with difficult landmarks, ultrasound can be of assistance [23]. We did not use ultrasound at the time of the study but have since implemented this for difficult cases.…”
Section: Kramer Et Al Described the Necessity Of Stylets In 23mentioning
confidence: 99%
“…5 In a difficult airway scenario, when combined with topical anesthesia of the nasal passages, superior laryngeal nerve block, transtracheal block, and appropriate decongestion of the airway, it is probably the safest and easiest technique. 6 However, its use has since declined because it is a blind procedure that needs more time than the better alternatives that came on the scene, like flexible fiberscope-guided techniques. All this led to a lack of appropriately skilled and trained personnel, bringing it further down in the preference order.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Previous studies have shown that sufficient airway anaesthesia is essential to suppress gag, swallow and cough reflexes prior to awake endotracheal intubation, and with the development of ultrasound visualisation technology, ultrasound-guided internal branch of the superior laryngeal nerve block (UGISLNB) has many benefits for awake nasotracheal intubation guided by an FB. 15,[23][24][25][26][27] However, the clinical application of UGISLNB in patients with COPD who develop severe respiratory failure and require fibreoptic nasotracheal intubation has not been studied. Hence, the purpose of this randomised controlled clinical trial is to assess the time for intubation, adverse events, comfort score and stress response to UGISLNB in patients with severe COPD undergoing awake fibreoptic nasotracheal intubation; to verify its safety and efficacy; and to provide a clinical reference.…”
Section: Introductionmentioning
confidence: 99%